The Role of Agenda Setting in the Construction of COVID-19 Vaccination Information: A Systematic Literature Review - Syelfa Putri Maharani (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
The COVID-19 pandemic has created new challenges, particularly in communication, where the media plays a crucial role in disseminating information regarding COVID-19 vaccination during the pandemic. Agenda Setting plays a significant role in shaping public perception regarding COVID-19 vaccination through media coverage. This study analyzes the role of Agenda Setting in vaccination coverage during the pandemic, using the Systematic Literature Review (SLR) method and the PRISMA approach with 8 relevant journal articles for analysis. The results indicate that the media can serve as a strategic tool in implementing Agenda Setting and disseminating information regarding vaccination; however, there are significant challenges in how information is presented and received by the public. This study confirms that while the media can act as a strategic tool in establishing Agenda Setting and disseminating information regarding vaccination, there are significant challenges in how information is presented and received by the public.